Metformin and gefitinib cooperate to inhibit bladder cancer growth via both AMPK and EGFR pathways joining at Akt and Erk - Peng, Mei (Sci Rep, 2016)
EGFR is a potential therapeutic target for treating bladder cancer, but has not been approved for clinical use yet. Metformin is a widely used antidiabetic drug and has demonstrated interesting anticancer effects on various cancer models, alone or in combination with chemotherapeutic drugs. The efficacy of gefitinib, a well-known EGFR tyrosine kinase inhibitor, combined with metformin was assessed on bladder cancer and underlying mechanisms were explored. This drug combination induced a strong anti-proliferative and anti-colony forming effect and apoptosis in bladder cancer cell lines. Gefitinib suppressed EGFR signaling and inhibited phosphorylation of ERK and Akt. Metformin amplified this inhibitory effect and enhanced gefitinib-induced activation of AMPK signaling pathway. In vivo intravesical treatment of metformin and gefitinib on syngeneic orthotopic mice confirmed the significant inhibitory effect on bladder tumor growth. These two drugs may be an excellent combination for the treatment of bladder cancer through intravesical instillation.